Carcass and meat quality characteristics from Iberian wild red deer (Cervus elaphus) hunted at different ages. (5th November 2018) - Maggiolino, Aristide; Pateiro, Mirian; Serrano, Martina P; Landete‐Castillejos, Tomás; Domínguez, Rubén; García, Andrés; Gallego, Laureano; De Palo, Pasquale; Lorenzo, José Manuel
Abstract: BACKGROUND: Deer‐meat consumption is increasing in several countries based on claims that it is a healthy red meat. This study assessed the effect of slaughter age (low – 26 months and younger; medium – from 27 months to younger than 42 months; and high – 42 months and older) on carcass characteristics and meat physicochemical properties of 150 Iberian wild red deer. RESULTS: Whole carcass yields of neck, backbone and flank increased ( P < 0.001) with age, while yields of shoulder, tenderloin and leg decreased ( P < 0.05) with age. The pH measured at 48 h post mortem at 9th rib level was not affected by age, while pH measured at 72 h post mortem at the longissimus thoracis et lumborum muscle decreased ( P < 0.05) with age. Meat chemical composition was not affected by slaughter age, except for intramuscular fat (IMF), which increased ( P < 0.05) with slaughter age. Finally, cooking loss and shear force were higher ( P < 0.05) in meat from older deer. CONCLUSION: Most characteristics of meat from wild red deer depend on age at slaughter. The greater IMF of meat from older animals may render it more palatable. However, meat shear force also increased with age. Additional studies testing palatability seem to be necessary to evaluate the effects of slaughter age on the sensorial quality of meat from Iberian wild red deer. © 2018 Society of Chemical Industry